1999
DOI: 10.1104/pp.119.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations of Lignins in Transgenic Poplars with Depressed Cinnamyl Alcohol Dehydrogenase or Caffeic AcidO-Methyltransferase Activity Have an Opposite Impact on the Efficiency of Industrial Kraft Pulping1

Abstract: We evaluated lignin profiles and pulping performances of 2-yearold transgenic poplar (Populus tremula ؋ Populus alba) lines severely altered in the expression of caffeic acid/5-hydroxyferulic acid O-methyltransferase (COMT) or cinnamyl alcohol dehydrogenase (CAD). Transgenic poplars with CAD or COMT antisense constructs showed growth similar to control trees. CAD downregulated poplars displayed a red coloration mainly in the outer xylem. A 90% lower COMT activity did not change lignin content but dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
277
2
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(298 citation statements)
references
References 33 publications
14
277
2
5
Order By: Relevance
“…Whereas the major alteration induced by the AtCAD-D mutation was the incorporation of sinapaldehyde units in lignins, differences in other structural traits were observed that were reminiscent of the traits reported for CAD-deficient poplars (Lapierre et al, 1999). The proportion of G lignin units with free .…”
Section: Lignin Modification In Mutantsmentioning
confidence: 94%
See 1 more Smart Citation
“…Whereas the major alteration induced by the AtCAD-D mutation was the incorporation of sinapaldehyde units in lignins, differences in other structural traits were observed that were reminiscent of the traits reported for CAD-deficient poplars (Lapierre et al, 1999). The proportion of G lignin units with free .…”
Section: Lignin Modification In Mutantsmentioning
confidence: 94%
“…The xylem of these transgenic plants exhibits a red coloration, and their lignins incorporate cinnamyl-aldehydes (Ralph et al, 1998). Two-and 4-year-old CAD antisense transgenic poplars contain less lignins than control plants (Lapierre et al, 1999;Pilate et al, 2002) and show important modifications of their lignin composition (increase of free phenolic compounds and accumulation of sinapaldehyde). Surprisingly, despite a reduction of the sinapyl to coniferyl alcohol ratio, no cinnamaldehydes were detected by thioacidolysis in CAD antisense alfalfa (Baucher et al, 1999).…”
mentioning
confidence: 99%
“…These trees had a reduction in lignin content of 5% and yielded pulp with a lower kappa. The higher lignin extractability was not caused by a change in the S/G ratio but instead by a high content of free phenolic groups (Lapierre et al 1999).…”
Section: Modifications In Lignin Content and Compositionmentioning
confidence: 99%
“…Both reactions are important for the introduction of methoxy groups at the aromatic ring which determine the extractability of lignin (see above). Significant changes of lignin content and S/G ratio in trees have been achieved by genetic engineering of 4CL (Hu et al 1999), F5H (Franke et al 2000), CCoAOMT (Meyermanns et al 2000), COMT (Tsai et al 1998 and CAD (Baucher et al 1996, Lapierre et al 1999.…”
Section: Modifications In Lignin Content and Compositionmentioning
confidence: 99%
“…A genetic transformation approach to produce transgenic eucalyptus trees with reduced lignin content or by modification of the lignin composition could make its removal easy with reduced usage of chemicals that might prove helpful to overcome the hurdles in quality paper-making. The monolignols, p-coumaryl, coniferyl and sinapyl alcohols give rise to the lignin polymer units such as p-hydroxyphenyl (H), guaiacyl (G), and syringyl (S) respectively that are linked by a series of ether and carbon-carbon linkages (Higuchi 1990;Lapierre et al 1999). Lignin rich in S units are more desirable than lignin rich in G units as the β-O-4-linkages of S units are more susceptible to chemical delignification process than the relatively stronger carbon-carbon bonds of G-units (Chiang et al 1988;Lapierre et al 1999).…”
Section: Altering Lignin Pathwaymentioning
confidence: 99%